Lymphatic vessel network injury reduces local tumor control despite preservation of the tumor-draining lymph node - Lauren N. Liebman; Yang Shen; Zachary S. Buchwald; Zhanna Nepiyushchikh; Zhiming Qi; Andrés J. García; J. Brandon Dixon (Scientific Reports)
Abstract The lymphatic system plays complex, often contradictory, roles in many cancers, including melanoma; these roles include contributions to tumor cell metastasis and immunosuppression in the tumor microenvironment as well as generation of antitumor immunity. Advancing our understanding of lymphatic vessel involvement in regulating tumor growth and immune response may provide new therapeutic targets or treatment plans to enhance the efficacy of existing therapies. We utilized a syngeneic murine melanoma model in which we surgically disrupted the lymphatic vessel network draining from the tumor to the tumor-draining lymph node (TDLN) while leaving the TDLN intact. Although transport of lymphatic-specific molecular weight tracers to the TDLN remains present after surgery, disruption of the tumor-draining lymphatic vessels results in decreased local tumor control, as reflected in an increase in the rate of tumor growth and reduction in effector-like T cell infiltration into the tumor. Our findings suggest that preservation of the functional tumor-draining lymphatic network may be essential in promoting a robust antitumor immune response.